Discovery and Characterisation of Castlerea Virus, a New Species of Negevirus Isolated in Australia. (22nd February 2017) - O'Brien, Caitlin A; McLean, Breeanna J; Colmant, Agathe M G; Harrison, Jessica J; Hall-Mendelin, Sonja; van den Hurk, Andrew F; Johansen, Cheryl A; Watterson, Daniel; Bielefeldt-Ohmann, Helle; Newton, Natalee D; Schulz, Benjamin L; Hall, Roy A; et al.
With advances in sequencing technologies, there has been an increase in the discovery of viruses that do not group with any currently described virus families. The newly described taxon Negevirus encompasses a group of viruses displaying an insect-specific phenotype which have been isolated from multiple host species on numerous continents. Using a broad-spectrum virus screening assay based on the detection of double-stranded RNA and next-generation sequencing, we have detected a novel species of negevirus, from Anopheles, Culex, and Aedes mosquitoes collected in 4 geographically separate regions of Australia. Bioinformatic analysis of the virus, tentatively named Castlerea virus, revealed that it is genetically distinct from previously described negeviruses but clusters in the newly proposed Nelorpivirus clade within this taxon. Analysis of virions confirmed the presence of 2 proteins of 24 and 40 kDa which support previous bioinformatic predictions of negevirus structural proteins.